Synthesis and molecular design of mono aspirinate thiourea-azo hybrid molecules as potential antibacterial agents - Zainab, Ngaini; Wan Zullkiplee, Wan Sharifatun H.; Abd Halim, Ainaa Nadiah (Taylor and Francis, 2021)
New mono aspirinate thiourea-azo derivatives 2a–f were synthesized using aspirin as a natural product-based precursor, with 4-aminophenylazophenol derivatives in excellent 70–90% yields. Overall, 2a–f gave excellent antibacterial activity against Staphylococcus aureus S48/81 and 2-(((3- ((2-bromophenyl)diazenyl)-4-hydroxyphenyl)carbamothioyl)carbamoyl)phenyl acetate (2d) exhibited a larger zone of inhibition 10mm, comparable to the standard ampicillin. The molecular docking analysis of 2d against S. aureus tyrosyl-tRNA synthetase protein displayed a free energy interaction of 7.7 kcal/mol compared to aspirin (6.4 kcal/mol).